2022
DOI: 10.1186/s13071-022-05326-3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Borrelia burgdorferi sensu lato in ticks and small mammals from different habitats

Abstract: Background Ixodid ticks are important vectors for zoonotic pathogens, with Ixodes ricinus being the most important in Europe. Rodents are hosts of immature life stages of I. ricinus ticks and are considered main reservoirs for tick-borne pathogens, e.g. Borrelia burgdorferi. The aim of this study was to analyse the prevalence as well as genospecies and sequence type (ST) diversity of Borrelia burgdorferi sensu lato in ticks and small mammals from central Germany and to elaborate on the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…Sequencing of 16S rDNA is considered a gold standard for the identification of ticks and many other organisms, including bacteria. However, I. ricinus could not be differentiated from I. inopinatus by the commonly used 16S rDNA fragment [ 13 , 16 ] due to the high haplotype diversity of this gene [ 8 , 10 , 11 , 16 , 22 25 ]. The COI gene is another common marker used for species delineation within the animal kingdom (e.g., the BOLD [Barcode of Life Data System] database); however, similarly to 16S rDNA, its analyses do not have the power to detect potential hybridization between closely related species.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of 16S rDNA is considered a gold standard for the identification of ticks and many other organisms, including bacteria. However, I. ricinus could not be differentiated from I. inopinatus by the commonly used 16S rDNA fragment [ 13 , 16 ] due to the high haplotype diversity of this gene [ 8 , 10 , 11 , 16 , 22 25 ]. The COI gene is another common marker used for species delineation within the animal kingdom (e.g., the BOLD [Barcode of Life Data System] database); however, similarly to 16S rDNA, its analyses do not have the power to detect potential hybridization between closely related species.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, persistent TBEV infection for up to 100 dpi was reported in an experimentally infected M. arvalis in a study conducted by Achazi et al [ 15 ]. However, M. arvalis voles are not a common rodent species in TBEV studies mainly because their main type of habitat is grasslands and not forests and woodlands, as it is for I. ricinus ticks and most common rodents in TBEV studies— A. flavicollis and C. glareolus [ 60 ]. Knap et al [ 16 ] have suggested that A. flavicollis rodents might be less susceptible to TBEV infection compared to C. glareolus , although it has been implied that the rate of infection in a specific species might depend on the year.…”
Section: Discussionmentioning
confidence: 99%
“…with ct-values <34 and on Borreliella spp.-positive samples if the ct-values were <35. MLST was carried out as described by Schmidt et al [ 59 ] and Król et al [ 60 ].…”
Section: Methodsmentioning
confidence: 99%